Challenges of distance English teaching: Narrative analysis of Iranian mainstream EFL teachers’ lived experiences - Fakharzadeh Mehrnoosh; Naderi Mohammad Hassan (ExELL (Explorations in English Language and Linguistics))
This study aimed to examine what challenges Iranian EFL teachers in the mainstream educational system experienced in distance classes during the COVID-19 pandemic. Telephone unstructured narrative interview was employed to collect data from 20 teacher participants, and two theoretical frameworks, CoI and TPACK, were used to interpret the results. The thematic narrative analysis yielded ten themes: non-customized platforms, material-related issues, connection/internet issues, pedagogical problems, evaluation problems, insufficiency of teachers’ knowledge of technology, unmet expectations, physical absence of teacher/student, student-related issues, and dealing with negative emotions. The authors discuss that while some challenges are the antecedent contextual challenges that existed and will probably continue to exist in the context of distance classes, some other challenges can be avoided if teachers are equipped with TPACK to fulfill their new roles in the community of distance classes.